2015
DOI: 10.1001/jamasurg.2014.678
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cancer Center When Using Lymph Node Count as a Quality Measure for Gastric Cancer Surgery

Abstract: Although adequate lymph node retrieval is more likely in hospitals with a recognized cancer program, survival outcome is associated with the lymph node count rather than with cancer program classification. Less than half of the cases reviewed in this study met the minimum lymph node-count guideline, indicating the need for process improvement for all hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 17 publications
4
57
0
Order By: Relevance
“…With respect to the relationship between lymph node count and survival, it has been reported that the removal of more than 25 lymph nodes was associated with improved survival. 2 This is in accordance with the results of Morgan et al 1 According to Japanese rules, a radical D2 lymphadenectomy is defined as extirpation of 26 or more lymph nodes. We also recommend the removal of more than 25 lymph nodes as a superior criterion for advanced gastric cancer.…”
supporting
confidence: 83%
See 2 more Smart Citations
“…With respect to the relationship between lymph node count and survival, it has been reported that the removal of more than 25 lymph nodes was associated with improved survival. 2 This is in accordance with the results of Morgan et al 1 According to Japanese rules, a radical D2 lymphadenectomy is defined as extirpation of 26 or more lymph nodes. We also recommend the removal of more than 25 lymph nodes as a superior criterion for advanced gastric cancer.…”
supporting
confidence: 83%
“…Regarding the insignificant difference in survival between hospitals with cancer program approval and hospitals without reported in Morgan et al, 1 we consider that hospital factors should be associated with abundant experience, a higher number of lymph nodes removed, a higher level of safety, and improved survival. In fact, our unpublished data show that patients treated by surgeons who specialized in gastric cancer surgery had better survival than patients treated by surgeons who did not.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The surgical specimens and lymph nodes were examined by pathologists specializing in gastric cancer using the updated edition of the UICC/ AJCC TNM staging system, which was then converted to the seventh edition at the time of our analysis [9]. For the purposes of the present study, the patients were divided into three groups according to the number of lymph nodes retrieved: patients with 15 harvested lymph nodes (LN 15), patients with 16-25 harvested lymph nodes (LN [16][17][18][19][20][21][22][23][24][25], and patients with >25 harvested lymph nodes (LN >25). The lymph node ratio (LNR) was defined as the ratio between metastatic and examined lymph nodes.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] Some patients who underwent the socalled "D2"dissection were actually D1 or D1 plus, with a locoregional recurrence rate of up to 41% according to the long-term results of a Dutch trial. 13 According to Morgan et al, 14 hospitals with cancer programme recognition have a higher probability to dissect 15 or more lymph nodes than their counterparts (45.5% vs 34.8%, respectively), which indicates variation in the surgical quality between hospitals. The uncertainty of operation highlights the importance of adjuvant CRT.…”
Section: Discussionmentioning
confidence: 99%